Look at This Key Words with Ladybird - 1b - W.Murray (China Ladybird Books Ltd., 2004)
Book 1b follows on from 1a and introduces 16 new words, including 'toys', 'has', 'trees' and 'ball'. Once this book has been completed, the child moves on to book 3b.